The anthropology of deep history1. (13th November 2014) - Gamble, Clive
<x xml:space="preserve">Abstract</x> The history of anthropology reveals a discipline driven by fission and fusion. In this article I use the framework of deep history as an example of what might be achieved if anthropology resolved to travel the road of fusion rather than continue with atomization. I will illustrate the pathway by examining the fusion of interdisciplinary endeavour that is encapsulated in the concept of a social brain. By placing social life at the heart of the historical process we find common ground for all the fields of anthropology, and beyond to other disciplines. Here anthropologists have the opportunity to set the agenda. The social brain works in deep as well as shallow history. It unites experimental and historical science. And it marks a return to those core principles which Lubbock and the founders of our Institute established.